Association between Vitamin D Level and Acne, and Correlation with Disease Severity: A Meta-Analysis - Yusuf Hasamoh (2022)
Background: Vitamin D deficiency is frequently associated with several medical conditions. However, a comprehensive meta-analysis assessing the association between vitamin D level and acne is lacking. Objective: To determine the relationship between vitamin D level and acne, and to assess the association between vitamin D level and acne severity. Methods: This meta-analysis was assessed by using the PubMed, EMBASE, Cochrane, and Scopus databases following the PRISMA guidelines. Serum/plasma 25-hydroxyvitamin D (25[OH]D) level, vitamin D deficiency, and the severity association between acne patients and healthy controls (HCs) were evaluated. The quality assessment was performed by using the Newcastle-Ottawa Scale. Results: Thirteen articles with a total of 1,362 acne patients and 1,081 HCs were included. The circulating 25(OH)D levels were significantly lower in patients with acne than in HCs (pooled MD = -9.02 ng/mL, 95% CI = -13.22 to -4.81, p < 0.0001). Vitamin D deficiency was more prevalent in acne patients than in HCs (pooled OR = 2.97, 95% CI = 1.68-5.23, I2 = 72%). Also, vitamin D levels were negatively correlated with acne severity. Conclusion: This meta-analysis demonstrated the significantly low vitamin D levels in acne patients. Also, there was evidence of an inverse association between vitamin D levels and acne severity. Therefore, vitamin D might be involved in the pathogenesis of acne.